A Study of The Various Employee Retention Strategies Adopted by IT Industry (International Journal of Scientific Research in Science and Technology, 2024)
In the rapidly changing landscape of the Information Technology (IT) sector, retaining employees has emerged as a significant challenge for organizations. This research investigates the diverse strategies that IT companies implement to keep skilled and capable personnel, with the goal of improving employee satisfaction and cultivating a constructive workplace atmosphere. It is a high-turnover industry that involves immense costs in recruitment, training, and onboarding procedures apart from the loss of vital knowledge and experience. A shortage of specialized IT skills is further caused by fast technologies and emerging trends related to cybersecurity, cloud computing, and artificial intelligence; therefore, it is quite relevant to have an appropriate mechanism for retaining employees. This study further identifies the impacts of retaining employees within an organization’s culture, employer branding, and stability in general. It concludes by highlighting routes for professional development and recognition, work-life balance, reduction of stress levels at work, and satisfaction with a job. IT organizations are warranted to ensure better employee engagement and higher levels of productivity if they focus more on professional growth and provide a supportive workplace allowing innovation and creativity. The findings of this study are important information for IT companies in the quest to remain competitive with appropriate employee retention practices. To forecast employee turnover, one can use a machine learning method like logistic regression. The system can detect trends and forecast the possibility of employees quitting the company by examining past data on employee demographics, job satisfaction, performance metrics, and other relevant factors. With the use of this predictive model, IT organisations may proactively handle potential employee retention problems and put focused retention initiatives into place.